Addressing Stroke Signs and Symptoms Through Public Education: The Stroke Heroes Act FAST Campaign - Cynthia L. Boddie-Willis, MD, MPH; Brianne M. Beagan, MPH; H. June O'Neill, MPH; Kathleen M. Foell, RD, MS; Hilary K. Wall, MPH (Centers for Disease Control and Prevention, 2008)
IntroductionIn 2003, only 18% of Massachusetts adults were aware of all signs and symptoms of stroke, but 80% would call 9-1-1 if they thought someone was having a stroke or heart attack. Because early recognition leads to early treatment and improved clinical outcomes, increasing symptom recognition could have an impact on stroke survival and stroke patients' quality of life.MethodsWe conducted secondary research to identify messages with evidence-based effectiveness for communicating stroke signs and symptoms. From these results, a Stroke Heroes Act FAST animation was created and concept-tested. Non-Hispanic white and non-Hispanic black women aged 40 to 64 years received education on stroke signs and symptoms. Knowledge change about stroke signs and symptoms was calculated immediately following and 3 months after the education session.ResultsUsing Stroke Heroes Act FAST educational materials that were developed, 72 women (mean age, 54 years; 15.5% were non-Hispanic blacks) received education about signs and symptoms of stroke and took the pretests and posttests to assess knowledge change. Immediately after the education session, significant increases were seen in the percentage of participants who recognized that facial droop (92% vs 99%, P = .02) and arm weakness or numbness (86% vs 97%, P = .004) were symptoms of stroke. Of the 65 participants who were given the 3-month follow-up survey, 100% remembered slurred speech and facial drooping as symptoms; 98.5% recalled arm weakness or numbness; and 97% would call 9-1-1 if they thought someone was having a stroke. None of these is a significant change from the posttest.ConclusionThe Stroke Heroes Act FAST kit may be a useful tool for improving knowledge of stroke signs and symptoms among adults.